Prevalence and Severity of COVID-19 Disease in Bangladesh: A Trend Analysis - Muyeed, Abdul (2020)
Objective: To investigate the prevalence and changes of events of COVID-19 disease by trending in Bangladesh. Methods: In this study, the daily time series data for nine weeks was used. The daily cases, case fatality rate (CFR), recovery-death-ratio (RDR) and percent changes (PC) associated with COVID-19 disease were used for prevalence and trending. Result: It is found that 68% males and 32% females patients were infected, among them 21 to 30 (26%) was the most and below 10 (3%) was the least infected age group until May 09. The approximate number of days for the infection, recovery and deaths to be doubled are 10, 5 and 18 respectively in Bangladesh as of May 09, 2020. The CFR of Bangladesh is found 1.55% which is less than the CFRs of the world (6.89%), Europe (9.17%), America (5.61%), Africa (3.26%) and South-East Asia (3.52%) as of May 09, 2020. The daily RDR exhibited a downward trend from April 04, 2020 to April 25, 2020 then showed an upward trend until May 09, 2020. Conclusion: The downward trending of the CFR indicates the death rate is low compared to diagnosis. The upward trend of the RDR indicates the recovery caused by COVID-19 is fast compared to deaths over time in Bangladesh. The downward trending of the PC indicates the cases percent of COVID-19 disease is reducing relative to three days prior cases.